2014
DOI: 10.5194/hess-18-2265-2014
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of a nonforecasted rain-on-snow flood in the Alps – a matter of model limitations or unpredictable nature?

Abstract: Abstract.A rain-on-snow flood occurred in the Bernese Alps, Switzerland, on 10 October 2011, and caused significant damage. As the flood peak was unpredicted by the flood forecast system, questions were raised concerning the causes and the predictability of the event. Here, we aimed to reconstruct the anatomy of this rain-on-snow flood in the Lötschen Valley (160 km 2 ) by analyzing meteorological data from the synoptic to the local scale and by reproducing the flood peak with the hydrological model WaSiM-ETH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 38 publications
2
141
0
1
Order By: Relevance
“…An enhanced version of the rainfall simulator described in Juras et al (2013Juras et al ( , 2016 was designed to achieve rain intensities close to observations during natural ROS events (Osterhuber, 1999;Rössler et al, 2014;Würzer et al, 2016). The new device was equipped by a Lechler 460.368.30.CA nozzle which was precisely calibrated in the laboratory and again on site.…”
Section: Rainfall Simulation and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced version of the rainfall simulator described in Juras et al (2013Juras et al ( , 2016 was designed to achieve rain intensities close to observations during natural ROS events (Osterhuber, 1999;Rössler et al, 2014;Würzer et al, 2016). The new device was equipped by a Lechler 460.368.30.CA nozzle which was precisely calibrated in the laboratory and again on site.…”
Section: Rainfall Simulation and Monitoringmentioning
confidence: 99%
“…ROS events have initiated severe floods in the past in many European countries such as Germany (HND Bayern, 2011;Sui and Koehler, 2001), Switzerland (Badoux et al, 2013;Rössler et al, 2014) and the Czech Republic (Čekal et al, 2011), as well as in North America (Ferguson, 2000;Kattelmann, 1997;Marks et al, 1998;McCabe et al, 2007;Pomeroy et al, 2016). Rainwater also affects snowpack stability which can initiate formation of wet snow avalanches (Ambach and Howorka, 1966;Baggi and Schweizer, 2008;Conway and Raymond, 1993) or trigger slushflows (Hestnes and Sandersen, 1987;Nyberg, 1989;Onesti, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no runoff is calculated, but the equivalent precipitation depth is related to the RoS event by its comparison to measured peak discharge during the event. However, even at the small catchment scale, Rössler et al (2014) concluded that the hydrometeorological conditions are the main factors quantifying RoS-driven flood events.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, cumulative rainfall and snowmelt can increase the magnitude of runoff and can thus generate much greater potential for flooding than a usual snowmelt event (Kattelmann, 1985;Marks et al, 1998). Besides their large damage potential, such events are also very difficult to forecast as shown by Rössler et al (2014) for a RoS-driven flood event in October 2011 in the Bernese Alps in Switzerland. Scientific interest has therefore increased in the last decades, and a number of different methods of analysis have been developed to better understand and quantify the physical processes by studying individual events in different locations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Correct estimations of snow cover and snowmelt distributions are therefore essential for accurate streamflow simulations (Maurer and Lettenmaier, N. Wever et al: Streamflow generation in an alpine catchment 2003; Berg and Mulroy, 2006;Seyfried et al, 2009;Koster et al, 2010). Additionally, rain-on-snow events may significantly increase the liquid water outflow from the snowpack (Mazurkiewicz et al, 2008;Wever et al, 2014a;Würzer et al, 2016Würzer et al, , 2017 and many flooding events have been caused by such events (Marks et al, 2001;Rössler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%